Hot target magnetron sputtering enhanced by RF-ICP source for CrNx coatings deposition. (September 2021) - Grudinin, V.A.; Sidelev, D.V.; Bleykher, G.A.; Yuriev, YuN.; Krivobokov, V.P.; Berlin, E.V.; Grigoriev, V. Yu; Obrosov, A.; Weiß, S.
Abstract: This article describes hot Cr target magnetron sputtering enhanced by a radio-frequency inductively coupled plasma (RF-ICP) source in an Ar + N2 atmosphere. Optical emission spectroscopy revealed an opportunity to perform magnetron sputtering in an inert (Ar) atmosphere, while the CrNx coating can be deposited on a substrate in a chemically reactive atmosphere formed by the RF-ICP source. High stability and repeatability of deposition process were observed, and the deposition rate of the CrNx coatings increased from 106 to 127 nm/min as N2 flow rate rose. The power of the RF-ICP source and the N2 flow rate can be used to tailor and control deposition conditions. The XRD and WDS measurements showed the effect of deposition conditions on the crystal structure and elemental composition of CrNx coatings. It was found that the change of substrate bias, RF-ICP source power and N2 flow rate result in variation of coating stoichiometry from pure Cr to CrN. Highlights: Separation of working atmospheres for sputtering and growth of compound coating. High-rate deposition of chromium nitride coatings. Deposition rate increases with higher reactive gas flow rate. Coating stoichiometry depends on power of RF-ICP source and nitrogen flow.